Video dubbing as a method for French pronunciation training: theory and practice - Kotuła, Krzysztof (Glottodidactica, 2018)
Pronunciation is an often-neglected aspect of language instruction. Teachers usually place the blame on lack of time and resources, as well as curricular restrictions. However, in recent years, we have witnessed a proliferation of various tools that can be used to render work on different aspects of pronunciation much more interesting. In the present paper, we will focus on one particular technique: video dubbing. By examining the answers provided by the participants of a dubbing project conducted by the author of the present study, we will try to reflect on the potential advantages of such activities, and determine whether they are considered stimulating and effective by language learners.